Urban and Architectural Heritage Conservation within Sustainability - Hmood, Kabila (IntechOpen, 2019)
Urban and Architectural Heritage within Sustainability is interested in the cities of the future, which must tie together the past, present, and future through an advanced connective chain that meets all humans' requirements in any era. This book attempts to answer many questions, such as what is urban conservation? How do cities of historical depth deal with modern planning policies and our conservation policies, rehabilitation, restoration, and preservation of historical cities and heritage buildings? How can we explain sustainable heritage and sustainability? Comprised of four sections, this book includes six chapters by noted experts and researchers. Section 1 covers heritage conservation and rehabilitation of architectural and urban heritage. Section 2 investigates current retrofitting strategies and interventions in heritage buildings through the viewpoint of energy efficiency. Section 3 redefines what identity is and explores how new places and spaces offer an eyrie of cultural values. And Section 4 establishes heritage significant values and assesses sustainable heritage conservation options.